1986
DOI: 10.2307/1165866
|View full text |Cite
|
Sign up to set email alerts
|

Development of Knowledge about the Appearance-Reality Distinction

Abstract: 7 studies of the acquisition of knowledge about the appearance-reality distinction suggest the following course of development. Many 3-year-olds seem to possess little or no understanding of the distinction. They fail the simplest Appearance-Reality (AR) tasks and are unresponsive to efforts to teach them the distinction. Skill in solving simple AR tasks is highly correlated with skill in solving simple perceptual Perspective-taking (PT) tasks; this suggests the hypothesis that the ability to represent the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
233
2
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 450 publications
(252 citation statements)
references
References 37 publications
11
233
2
6
Order By: Relevance
“…A total of only 3.0 incongruous responses was produced. Thus, whereas the mean number of correct response patterns is comparable to numbers reported by Flavell (e.g., Flavell et al, 1983Flavell et al, , 1987Flavell et al, , 1986, our participants showed more one-sided intellectual realism. This may be because our objects were somewhat less deceptive, with more obvious functions, than those used by Flavell and colleagues.…”
Section: Appearance-reality Tasksupporting
confidence: 79%
See 4 more Smart Citations
“…A total of only 3.0 incongruous responses was produced. Thus, whereas the mean number of correct response patterns is comparable to numbers reported by Flavell (e.g., Flavell et al, 1983Flavell et al, , 1987Flavell et al, , 1986, our participants showed more one-sided intellectual realism. This may be because our objects were somewhat less deceptive, with more obvious functions, than those used by Flavell and colleagues.…”
Section: Appearance-reality Tasksupporting
confidence: 79%
“…The importance of lexical development for polynomy is demonstrated not only by ~0 Ray (1996) found a relationship between children's performance on object property (e.g., color) and object identity appearance-reality tasks, r = .48, p < .0l. (Flavell et al, 1986, also found such a relation but did not control for age, rendering it uninterpretable. Ray partialed out age.)…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations